Status of Nepalese Tea Trade in Global Market - Shrestha, Ram Krishna (PYC Nepal Journal of Management, 2010)
The development of tea industry in Nepal took momentum after the private sector involved in tea market. Nepal is rich in the ecosystem and bio-diversity with tremendous agricultural opportunities wherein tea is grown as among the major cash crops. Tea business has been emerging as a potential export trade of Nepal. The growth and expansion of this sector has been steadily progressive with increased competitiveness and market orientation. An attempt has been made in this article to elucidate the challenges and opportunities faced by tea exporting businessman and trend of tea trade in global perspective. The tea industry has entered into the global market inviting cumbersome challenges and greater potentialities. Nepal's membership into the WTO has been increase competition and possibilities in the tea sector. The provisions of various WTO related rules, regulations and obligations has demanded reforms regarding the productions and marketing practices in the industry. The maintenance of standards and quality under the law of WTO has been compulsory for the export / import trade of tea. The country has to cope with Sanitary and Phytosanitary, Technical Tariffs Regulations, Standards and self guards etc. provisions. There have been both challenges and opportunities in tea business for Nepal. The country has to be able to exploit the opportunities for promotion and development of tea business. Had there been appropriate technologies, research and good marketing practices, country would have enjoyed a lot of monetary advantages out of tea business. The absence of advanced and appropriate technology, good human resource, lab facilities have created challenges to tea businessmen for doing business at global level. Because of these challenges, Nepal has to export high quality leaf tea to India at a very cheap price.